Gut–Brain Axis in Regulation of Blood Pressure - Yang, Tao; Zubcevic, Jasenka (Frontiers in Physiology, 2017)
Hypertension (HTN) is an escalating health issue worldwide. It is estimated that 1.56 billion people will suffer from high blood pressure (BP) by 2025. Recent studies reported an association between gut dysbiosis and HTN, thus proposing interesting avenues for novel treatments of this condition. The sympathetic nervous system (SNS) and the immune system (IS) play a recognized role in the onset and progression of HTN, while reciprocal communication between gut microbiota and the brain can regulate BP by modulating the interplay between the IS and SNS. This review presents the current state of the science implicating brain-gut connection in HTN, highlighting potential pathways of their interaction in control of BP.